An Unusual Case of a Patient With a Chemical Burn of the Esophagus and Gastric Perforation - S. A. Domrachev; N. O. Solovyev (Неотложная медицинская помощь)
Treatment of patients with chemical burns of the esophagus and stomach is a difficult task.Perforation of the stomach or the formation of strictures of the esophagus, stomach, duodenum, and even the initial parts of the jejunum can be the outcome of chemical burns.Patients with concomitant esophageal and gastric strictures are the most difficult to treat, which often requires multi-stage operations.This article describes a clinical case of surgical treatment of a patient with a combined chemical burn of the esophagus and stomach with hydrochloric acid. One week after hospitalization, the patient had gastric perforation. The patient was urgently operated in the course of peritonitis. The peculiarity of the operation was that the surgeons, having made a gastrectomy, removed the esophageal stump to the anterior abdominal wall in the epigastrium and applied an enterostomy. In such a state with significant alimentary depletion (body mass index — BMI 15) on 11.10.02 the patient was taken to a Moscow clinic. A year later, the main surgical reconstructive treatment was performed — retrosternal bypass esophagoplasty of the right half of the large intestine and the terminal ileum in the isoperistaltic position, as well as extirpation of the esophagus. As a result of long-term treatment and several surgical interventions, a good short-term and long-term result was obtained.